Assessment of asymptomatic Leishmania infection in people living with HIV: a long-term follow-up study in Northeastern Brazil - Aguiar, Matheus Henrique Gonçalves; Guedes, Diego Lins; Júnior, Walter Lins Barbosa; da Silva, Elis Dionísio; Bezerra, Gilberto Silva Nunes; Bonfim, Cristine Vieira; Vieira, Amanda Virginia Batista; Monteiro, Bruna Eduarda Freitas; dos Santos Souza, Roberta; Diniz, Lucyo Flávio Bezerra; de Aquino, Samuel Ricarte; Mendes, Luiz Gustavo; et al. (Frontiers in Medicine, 2025)
In people living with HIV (PLWH), surveillance for Leishmania infection is crucial for identify those at risk of developing visceral leishmaniasis (VL). Leishmania-HIV coinfection worsens patient outcomes and increases mortality and relapse rates. We conducted a prospective study (2017–2023) in Northeast Brazil to assess the long-term outcomes of asymptomatic Leishmania-HIV coinfected outpatients and Leishmania-negative PLWH. Participants were drawn from a cross-sectional study performed in 2017, which identified both Leishmania-HIV coinfected and Leishmania-negative PLWH. Epidemiological, clinical, and laboratory data were collected from medical records (2017–2023). In 2023, these individuals were retested for Leishmania using serological tests and conventional polymerase chain reaction (PCR). Categorical variables were compared using the chi-square test, and non-parametric tests were used for quantitative variables. During follow-up, six individuals developed VL: five from the coinfected group and one from the non-coinfected PLWH group (OR 10.4; 95% CI 1.2–94.2; p = 0.023). Three patients experienced relapse: one from the PLWH group and two from the coinfected group. There was one death in the Leishmania-HIV group. In 2023, 80 patients were retested; five coinfected patients remained positive for VL by one or more tests, and two PLWH patients seroconverted for VL. Our findings underscore the critical need for long-term follow-up of asymptomatic Leishmania-HIV patients to mitigate disease progression and associated complications.